Análise de segurança de esquemas de privacidade de dados - Oliveira, Heveraldo Rodrigues de (2007)
This dissertation walks through the Advantage Function Model, from Goldwasser and Bellare, explaining its complex concepts and exemplifying its application in the analysis of encryption security schemes currently used in practice. It is also shown ways to put this model into practice. The safety of the schemes used in the IEEE 802.11 Standard are explained and used as the object of study in the model application. The results can be used to justify the adoption of certain security technologies. The analysis presented demonstrates the great value of its study and of the use of mathematical models in safety demonstrations. It can help designers and developers to maximize the safety of their encryption schemes, by the effective application of the model or by the simple understanding of the concepts of security mentioned here.